Bovine papilloma virus deoxyribonucleic acid: a novel eucaryotic cloning vector. - Sarver, N (1981)
A novel eucaryotic vector derived from the transforming region of bovine papilloma virus was established and demonstrated to be highly effective for introducing foreign genes into animal cells. The foreign deoxyribonucleic acid (DNA) is replicated and actively transcribed as an episome, and the transcripts are translated into an authentic gene product. We have constructed a DNA hybrid molecule, BPV69T-rI1, containing the transforming region of bovine papilloma virus DNA and the rat preproinsulin gene I (rI1), and used it to transform susceptible mouse cells. DNA hybridization analysis has demonstrated the presence of multiple unintegrated copies of hybrid DNA molecules, with the bovine papilloma virus 1 DNA segment and the rI1 gene covalently linked in selected transformed cell lines. S1 nuclease analysis revealed the presence of a correctly spliced coding segment of the preproinsulin transcript similar or identical in its electrophoretic mobility to that of messenger ribonucleic acid produced in rat insulinoma cells. Significant levels of a protein immunoreactive with anti-insulin serum were detected by radioimmunoassay in the culture medium of transformed cells. Immunoprecipitation analysis in conjunction with competitive binding to bovine proinsulin established the identity of the protein as that of rat proinsulin.